Arg-substituted VmCT1 analogs reveals promising candidate for the development of new antichagasic agent. Issue 14 (2nd December 2020) - Pedron, Cibele Nicolaski; Freire, Katielle Albuquerque; Torres, Marcelo Der Torossian; Lima, Dânya Bandeira; Monteiro, Marília Lopes; Menezes, Ramon Róseo Paula Pessoa Bezerra de; Martins, Alice Maria Costa; Oliveira, Vani Xavier
Abstract: VmCT1 is an antimicrobial peptide (AMP) isolated from the venom of the scorpion Vaejovis mexicanus with antimicrobial, anticancer and antimalarial activities, which the rational design with Arg-substitution has yielded AMPs with higher antimicrobial activity than VmCT1. Chagas is a neglected tropical disease, becoming the development of new antichagasic agents is urgent. Thus, we aimed to evaluate the antichagasic effect of VmCT1 and three Arg-substituted analogues, as well their action mechanism. Peptides were tested against the epimastigote, trypomastigote, amastigote forms of Trypanossoma cruzi Y strain and against LLC-MK2 mammalian cells. The mechanism of action of these peptides was evaluated by means of flow cytometry and scanning electron microscopy. VmCT1 presented activity against all three forms of T. cruzi, with EC50 against trypomastigote forms of 1.37 μ mol L −1 and selectivity index (SI) of 58. [Arg] 3 -VmCT1, [Arg] 7 -VmCT1 and [Arg] 11 -VmCT1 also showed trypanocidal effect, but [Arg] 11 -VmCT1 had the best effect, being able to decrease the EC50 against trypomastigote forms to 0.8 μ mol L −1 and increase SI to 175. Necrosis was cell death pathway of VmCT1, as well [Arg] 7 -VmCT1 and [Arg] 11 -VmCT1, such as observed by membrane damage in flow cytometry analyses and scanning-electron-microscopy. In conclusion, [Arg] 11 -VmCT1 revealed promising as a candidate for new antichagasic therapeutics.